Systemic Venous Return Abnormality Associated with An Abnormality of Total Pulmonary Venous Return - Abdelbaki, Mourad; Bourida, Wahib; Boureghda, A.; ., Roudoci (Clinical Medicine And Health Research Journal, 2023)
This is a 9-year-old child hospitalized for an intraoperative partial venous return anomaly and after an exploration we found a complex congenital cardiac pathology such as an anomaly of total venous return associated with an anomaly of systemic venous return which is mainly seen at early ages Mots-clés Anomalie de retour veineux systémique, Anomalie de retour veineux pulmonaire total, Collecteur Confluence pulmonaire, Urgence néonatale